European Conference on Cognitive Ergonomics 2021 2021
DOI: 10.1145/3452853.3452883
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Assembly Workstations and cobots: a qualitative assessment involving senior and adult workers

Abstract: Collaborative robots (cobots) are increasingly installed at manufactory plants to keep up with the market demands, combining the benefits of advanced automation and flexible production machines. Yet, the workers' acceptance of this technology is crucial to fully exploit their potential and to make cobots a valuable support for operators themselves. The present paper reports and discusses the preliminary results of a semi-structured interview study, which investigates how adult workers of different age groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…This new industrial revolution emerged in response to the increasing automation and removal of human workers from manufacturing processes, which was a hallmark of Industry 4.0. Industry 5.0 seeks to address these shortcomings by advocating for the reintroduction of human workers for instance alongside robots and collaborative robots (cobots; Faccio et al, 2023;Huang et al, 2022;Pluchino et al, 2023;Rossato et al, 2021aRossato et al, , 2021b, thus combining the strengths of humans and machines (Nahavandi, 2019). Industry 5.0 focuses on merging the creativity and expertise of human experts with efficient and intelligent machines.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This new industrial revolution emerged in response to the increasing automation and removal of human workers from manufacturing processes, which was a hallmark of Industry 4.0. Industry 5.0 seeks to address these shortcomings by advocating for the reintroduction of human workers for instance alongside robots and collaborative robots (cobots; Faccio et al, 2023;Huang et al, 2022;Pluchino et al, 2023;Rossato et al, 2021aRossato et al, , 2021b, thus combining the strengths of humans and machines (Nahavandi, 2019). Industry 5.0 focuses on merging the creativity and expertise of human experts with efficient and intelligent machines.…”
Section: Introductionmentioning
confidence: 99%
“…The enablers of Industry 5.0 include infrastructure, communication, and automation technology, which are instrumental in improving working-life quality, increasing efficiency, and driving innovation (Ivanov, 2023). Among the Industry 5.0 technologies, there are: digital twins and digital simulation (Nenna et al, 2023a(Nenna et al, , 2023bXu et al, 2021), that is, digital replicas of physical objects or systems, allowing real-time monitoring, analysis, and optimization of industrial processes; cobots (Faccio et al, 2023;Huang et al, 2022;Pluchino et al, 2023;Rossato et al, 2021aRossato et al, , 2021b, robots designed to work alongside humans, enhancing productivity and safety in manufacturing environments; Internet of Things (IoT) and Internet of Everything (IoE), that is, connects devices, objects, and people to enable intelligent communication, data exchange, and automation; artificial intelligence (AI; Xu et al, 2021) which empowers machines to perform cognitive tasks, decision-making, and learning, enhancing productivity and efficiency; and big data analytics, that permit the analysis of large volumes of data to extract valuable insights, optimize operations, and enable data-driven decision-making (Maddikunta et al, 2022;Xu et al, 2021). Xu et al (2021) also reported two other categories of technologies: individualized human-machine interaction technologies that aim to interconnect and combine the strengths of humans and machines, enabling seamless collaboration and interaction; bio-inspired technologies and smart tools, which involve the use of materials with embedded sensors and enhanced features that are recyclable, promoting sustainability and innovation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of studies have investigated the impact of introducing emerging technologies such as robots and automation in the workplace (e.g., [6,52,65]), focusing on various aspects including social interactions [69,70,83], safety [64,67], work organization [42,113], or the importance of worker involvement and acceptance [48,63,65,88,103].…”
Section: Introduction Of Cobots In the Workplacementioning
confidence: 99%
“…In a similar vein, Charalambous et al [17] focused on organizational human factors that must be considered in order to help organizations successfully introduce robots, and operator participation in the implementation process was highlighted as a critical part [12,53]. The degree of worker involvement in the cobot adaption (e.g., [63,69,88]) has also been emphasized as it may significantly shape workers' perceptions of cobots [28].…”
Section: Introduction Of Cobots In the Workplacementioning
confidence: 99%